Trajectory of the main GABAergic interneuron populations from early development to old age in the rat primary auditory cortex - Lydia eOuellet; Etienne ede Villers-Sidani (Frontiers Media S.A., 2014)
In both humans and rodents, decline in cognitive function is a hallmark of the aging process, the basis for this decrease has yet to be fully characterized. However, using aged rodent models, deficits in auditory processing have been associated with significant decreases in inhibitory signaling attributed to a loss of GABAergic interneurons. Not only are these interneurons crucial for pattern detection and other large-scale population dynamics, but they have also been linked to mechanisms mediating plasticity and learning, making them a prime candidate for study and modelling of modifications to cortical communication pathways in neurodegenerative diseases. Using the rat primary auditory cortex (A1) as a model, we probed the known markers of GABAergic interneurons with immunohistological methods, using antibodies against gamma aminobutyric acid (GABA), parvalbumin (PV), somatostatin (SOM), calretinin (CR), vasoactive intestinal peptide (VIP), choline acetyltransferase (ChAT), neuropeptide Y (NPY) and cholecystokinin (CCK) to document the changes observed in interneuron populations across the rat's lifespan. This analysis provided strong evidence that several but not all GABAergic neurons were affected by the aging process, showing most dramatic changes in expression of parvalbumin (PV) and somatostatin (SOM) expression. With this evidence, we show how understanding these trajectories of cell counts may be factored into a simple model to quantify changes in inhibitory signalling across the course of life, which may be applied as a framework for creating more advanced simulations of interneuronal implication in normal cerebral processing, normal aging, or pathological processes.